On the long-run unemployment, inflation, and volatility - Stefano Fasani (Queen Mary University of London, School of Economics and Finance, 2021)
This paper builds up a simple New Keynesian model and revisits the relationship between unemployment and inflation in the long-run. It finds that when the labor market is affected by downward nominal wage rigidity, this relationship goes beyond the tradeoff between the first moments of unemployment and inflation provided by the short-run Phillips curve. Higher volatility in inflation raises unemployment at low-frequency. Increased volatility in inflation makes nominal wages more volatile but the rigidity constrains downward adjustments. Unemployment is more likely to increase above the natural level to guarantee the equilibrium in the labor market. The positive long-run co-movement between unemployment and inflation volatility is confirmed when tested using data from OECD countries.
Keywords: E24; E31; C23; 330; Unemployment; Inflation Volatility; DNWR; Panel regressions